2015
DOI: 10.1111/bph.13034
|View full text |Cite
|
Sign up to set email alerts
|

AT‐1001: a high‐affinity α3β4 nAChR ligand with novel nicotine‐suppressive pharmacology

Abstract: The α3β4 subtype of nicotinic acetylcholine receptors (nAChRs) has been implicated in mediating nicotine reinforcement processes. AT-1001 has been recently described as a high-affinity and selective α3β4 nAChR antagonist that blocks nicotine self-administration in rats. The aim of this study was to investigate the mechanism of action underlying the nicotine-suppressive effects of AT-1001

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
56
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 33 publications
(66 citation statements)
references
References 48 publications
8
56
0
Order By: Relevance
“…We have previously shown that AT-1001 blocks nicotine self-administration [26] and nicotine-induced reinstatement in rats [29], at doses similar to those in this study, at which it showed a decrease in acquisition of cocaine CPP and blockade of cocaine-induced behavioral sensitization. Nicotine and cocaine addiction often occur as co-morbid addictions, and human clinical and epidemiological reports show that cocaine-dependent individuals exhibit higher rates of cigarette smoking [52, 53], while cigarette smoking can predispose adolescent individuals to other forms of drug abuse [54].…”
Section: Discussionsupporting
confidence: 71%
See 2 more Smart Citations
“…We have previously shown that AT-1001 blocks nicotine self-administration [26] and nicotine-induced reinstatement in rats [29], at doses similar to those in this study, at which it showed a decrease in acquisition of cocaine CPP and blockade of cocaine-induced behavioral sensitization. Nicotine and cocaine addiction often occur as co-morbid addictions, and human clinical and epidemiological reports show that cocaine-dependent individuals exhibit higher rates of cigarette smoking [52, 53], while cigarette smoking can predispose adolescent individuals to other forms of drug abuse [54].…”
Section: Discussionsupporting
confidence: 71%
“…However, 18-MC is not very selective for the α3β4 nAChR [40], and it cannot be ruled out that other neurotransmitter systems contribute to the anti-addictive effects of 18-MC. In contrast, AT-1001 and AT-1012 have nanomolar affinity for the human and rat α3β4 nAChR, are >80-fold selectivity for the α3β4 nAChR compared to the α4β2 and α7 nAChR [26, 27, 29] and do not significantly bind to other non-nicotinic receptors [26]. We recently showed that AT-1001 has low efficacy partial agonist activity at the human α3β4 nAChR transfected into oocytes, showing approximately 30% of the efficacy of acetylcholine [28].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Systemic administration of the α7* nAChR agonist ABT-107, and the α4β2*/α6β2* agonist ABT-089 attenuates the reinstatement of nicotine seeking indicating an important role for α7* nAChRs and α4-, α6-, and β2-containing nAChRs, respectively, in this behavioral response [101]. A more recent study found that systemic administration of the α3β4* nAChR ligand AT-1001 decreases nicotine priming-induced reinstatement of drug seeking [102]. This emerging literature expands our understanding of the role of nAChR subtypes in nicotine seeking and identifies potential new targets for novel smoking cessation pharmacotherapies.…”
Section: Neurotransmitter Mechanisms Regulating Nicotine Seekingmentioning
confidence: 99%
“…As we have emphasized throughout this review, the identification of novel therapeutic targets can be strongly informed and guided by preclinical investigations in rodent models of nicotine addiction, including the reinstatement model of smoking relapse. Indeed, much of our understanding of the dopaminergic, glutamatergic, and cholinergic mechanisms underlying nicotine seeking and relapse behavior has been delineated from research in rodent models [67, 71, 87, 91, 92, 102]. Mechanistically, different neurotransmitter systems also interact to influence nicotine-seeking behavior and smoking relapse.…”
Section: Concluding Remarks and Future Considerationsmentioning
confidence: 99%